Misinformation During the Coronavirus Disease 2019 Outbreak: How Knowledge Emerges From Noise. (April 2020) - Rochwerg, Bram; Parke, Rachael; Murthy, Srinivas; Fernando, Shannon M.; Leigh, Jeanna Parsons; Marshall, John; Adhikari, Neill K. J.; Fiest, Kirsten; Fowler, Rob; Lamontagne, François; Sevransky, Jonathan E.
Abstract : Objectives: Although the amount of information generated during this most recent coronavirus disease 2019 pandemic is enormous, much is of uncertain trustworthiness. This review summaries the many potential sources of information that clinicians turn to during pandemic illness, the challenges associated with performing methodologically sound research in this setting and potential approaching to conducting well done research during a health crisis. Data Sources: Not applicable. Study Selection: Not applicable. Data Extraction: Not applicable. Data Synthesis: Not applicable. Conclusions: Pandemics and healthcare crises provide extraordinary opportunities for the rapid generation of reliable scientific information but also for misinformation, especially in the early phases, which may contribute to public hysteria. The best way to combat misinformation is with trustworthy data produced by healthcare researchers. Although challenging, research can occur during pandemics and crises and is facilitated by advance planning, governmental support, targeted funding opportunities, and collaboration with industry partners. The coronavirus disease 2019 research response has highlighted both the dangers of misinformation as well as the benefits and possibilities of performing rigorous research during challenging times.